Mortality prediction of laying hens due to heat waves - Riquena, Rodrigo; Pereira, Danilo; Vale, Marcos; Salgado, Douglas (Revista Ciência Agronômica, 2018)
Mortality in the production of laying hens is a concern for producers and constitutes a considerable economic loss. Some climatic events, such as heat waves, are directly related to the mortality increasing. The aim of this study was to relate the occurrence of heat waves with laying hens mortality, considering the effect of two different kinds of shed used in egg production. Daily mortality data were obtained from two aviaries located in the city of Bastos-SP for the period of October 2014 to January 2016. The data about the climate were gotten from two meteorological stations located in the cities of Tupã-SP and Rancharia-SP, Brazil, from 2010 to 2015. The heat waves were classified in the climatic database using different definitions recommended in the literature (FRICH et al., 2002; INSTITUTO NACIONAL DE METEOROLOGIA, 2016; ROSSATO; SARTORI; MISSIO, 2003 TEBALDI et al., 2006). Mortality and climate data were related in a single database and were classified into normal and high mortality by data mining using the J48 algorithm. It was possible to associate the occurrences of heat wave and the increase of mortality of laying hens. The classification tree generated identified accurately 71% of occurrences of high mortality and 95% of all mortality data. The classification tree allowed to relate the increase in laying mortality in function of heat waves and allows a prediction of when there will be a bigger chance of high mortality.